2010
DOI: 10.1002/ange.201001149
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Control of Cell Signaling and Growth by Magnetic Nanoparticles

Abstract: Magnetisch angezogen: Zellaktivitäten künstlich zu steuern gelingt durch nanoskalige magnetisch aktivierte zelluläre Signalgebung, wofür magnetische Nanopartikel selektiv an Zelloberflächenrezeptoren geknüpft und durch ein externes Magnetfeld aggregiert werden. Diese mechanozelluläre Aktivierung löst die nachgeschaltete Signalgebung aus und initiiert im Präangiogenese‐Stadium von Endothelzellen die Tubulogenese (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…92b, 104 Moreover, receptor-mediated artificial triggering of cell growth in preangiogenesis, which is a vital process both for the growth and development of blood vessels and for tumor metastasis stage 105 , has been successfully controlled by magnetic antibody-conjugated NPs binding the Tie2 receptor. 106 …”
Section: Activation Of Mechanotransduction Receptors and Mechano-sensmentioning
confidence: 99%
“…92b, 104 Moreover, receptor-mediated artificial triggering of cell growth in preangiogenesis, which is a vital process both for the growth and development of blood vessels and for tumor metastasis stage 105 , has been successfully controlled by magnetic antibody-conjugated NPs binding the Tie2 receptor. 106 …”
Section: Activation Of Mechanotransduction Receptors and Mechano-sensmentioning
confidence: 99%
“…An additional advantage of using these two types of external stimuli is that they can be applied and removed instantaneously, and thus pave the way towards fabricating materials whose structures and properties can be modulated 'on demand'. For example, magnetic fields have been used to control the movement and assembly of magnetite [6][7][8] , cobalt 9,10 and other 11 superparamagnetic NPs, which gives rise to diverse functions and applications, including magnetically switchable catalysis 12,13 , water purification 14 and the remote control of intracellular signalling 15,16 . Despite these advances, this strategy requires magnetically responsive components.…”
mentioning
confidence: 99%
“…The manipulation and control of cells and sub-cellular structures through the magnetic nanoparticle-based actuation (nanomagnetic actuation) of cellular processes is a hot research topic (33)(34)(35). Recent studies have demonstrated that it is possible to manipulate and control cell function with an external magnetic field and specific magnetic labeling of the cell surface receptors (36,37).…”
Section: Discussionmentioning
confidence: 99%